2008
DOI: 10.1143/jjap.47.1140
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Well-Aligned Al Nanowire Array Embedded in Si Matrix Using Limited Spinodal Decompositon

Abstract: The morphology of a phase-separated binary film during spinodal decomposition, whose evolution is limited on the growth surface, is studied. The temporal evolution of the Cahn-Hilliard equation without the elastic energy term under frozen bulk approximation is solved to investigate the possibility of well-aligned nanostructures. The model simulation showed that the well-aligned phase pattern on the top surface can be formed when surface diffusion length was optimized and film thickness was larger than a certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Many of these metals have similar masses to each other, which points to the critical role of chemistry in these samples, as opposed to kinetics. Alternatively, in the regime of ion-assisted deposition of binary materials, a growing body of experimental evidence has documented the formation of 3D structures including vertically-organized alternating material layers [26] and laterally-organized nanowires [24]. These structures are consistent with numerical studies of phase separation during film growth [38] or at moving fronts more generally [39].…”
Section: Potential Application To Other Regimessupporting
confidence: 57%
See 3 more Smart Citations
“…Many of these metals have similar masses to each other, which points to the critical role of chemistry in these samples, as opposed to kinetics. Alternatively, in the regime of ion-assisted deposition of binary materials, a growing body of experimental evidence has documented the formation of 3D structures including vertically-organized alternating material layers [26] and laterally-organized nanowires [24]. These structures are consistent with numerical studies of phase separation during film growth [38] or at moving fronts more generally [39].…”
Section: Potential Application To Other Regimessupporting
confidence: 57%
“…Motivated by a growing body of experimental [24][25][26][27] and numerical [24,28] evidence suggesting that phase separation plays an important role in pattern formation during the irradiation of two-component targets, and molecular dynamics simulations suggesting that existing theories neglecting this phenomenon may not explain the patterns [30], we have presented a generalization of the Bradley-Shipman theory of irradiated binary compounds [21,22] that admits the phase separation mechanism. We demonstrated that the resulting model readily admits the development of ordered patterns even for parameter values where the BS theory cannot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinodal decomposition in thin films can certainly lead to periodical nanostructures [26][27][28]. During film deposition, spontaneous spinodal decomposition has been shown to lead to either LCMs [29] or VCMs [30]. However, a comprehensive model that can predict LCM and VCM microstructures observed in experiments as function of materials parameters and processing conditions seems still lacking.…”
mentioning
confidence: 99%